Effect of intraoperative nerve monitoring on postoperative vocal cord palsy rates after thyroidectomy: European multicentre registry-based study. Issue 5 (16th June 2020) - Staubitz, J I; Watzka, F; Poplawski, A; Riss, P; Clerici, T; Bergenfelz, A; Musholt, T J; Riss, P; Slycke, S; Iacobone, M; Brunaud, L; Bergenfelz, A; et al.
Abstract: Background: Intraoperative nerve monitoring (IONM) of the recurrent laryngeal nerve (RLN) predicts the risk of vocal cord palsy (VCP). IONM can be used to adapt the surgical strategy in order to prevent bilateral VCP and associated morbidity. Controversial results have been reported in the literature for the effect of IONM on rates of VCP, and large multicentre studies are required for elucidation. Methods: Patients undergoing first-time thyroidectomy for benign thyroid disease between May 2015 and January 2019, documented prospectively in the European registry EUROCRINE®, were included in a cohort study. The influence of IONM and other factors on the development of postoperative VCP was analysed using multivariable regression analysis. Results: Of 4598 operations from 82 hospitals, 3542 (77·0 per cent) were performed in female patients. IONM was used in 4182 (91·0 per cent) of 4598 operations, independent of hospital volume. Postoperative VCP was diagnosed in 50 (1·1 per cent) of the 4598 patients. The use of IONM was associated with a lower risk of postoperative VCP in multivariable analysis (odds ratio (OR) 0·34, 95 per cent c.i. 0·16 to 0·73). Damage to the RLN noted during surgery (OR 24·77, 12·91 to 48·07) and thyroiditis (OR 2·03, 1·10 to 3·76) were associated with an increased risk of VCP. Higher hospital volume correlated with a lower rate of VCP (OR 0·05, 0·01 to 0·13). Conclusion: Use of IONM was associated with a low rate of postoperative VCP. Graphical Abstract: The influence of intraoperative nerve monitoring (IONM) and other factors on the development of postoperative vocal cord palsy (VCP) was assessed using multivariable regression analysis. In a cohort of 4598 patients from 82 hospitals, IONM was used in over 90 per cent of those treated by primary thyroidectomy for underlying benign thyroid disease. IONM reduced the rate of postoperative VCP. Intraoperative nerve monitoring associated with lower rates of vocal cord palsy